Engineering particle size distribution of sintered lightweight aggregates manufactured from waste coal combustion ash - Alqenai Yousif; Risdanareni Puput; Zooyousefin Mohammadamin; Nguyen Thuy; Farnam Yaghoob (E3S Web of Conferences, 2023)
Converting waste coal combustion ash (W-CCA) from power plants into novelty lightweight aggregates (LWA) is a viable and sustainable solution. Utilizing this waste material to produce a useful product for the concrete industry requires that the manufactured LWA adhere to industrial material regulations. This study focuses on engineering laboratory manufactured LWA to achieve aggregate gradation that meets the ASTM C330 standard. A systematic study that manipulates the degree of saturation during W-CCA paste preparation was adopted to understand the effect of moisture on LWA gradation. The degree of saturation was assessed based on the liquid (water) to solid ratio required to manufacture W-CCA paste. The investigation only alters the amount of water and recorded the gradation for fine LWA (FLWA), coarse LWA (CLWA), and combined coarse and fine LWA. L/S ratio of 0.33 achieved ASTM C330 required gradation for FLWA. A combination of L/S ratio of 0.33 and 0.34 achieved ASTM C330 required gradation for combined coarse and fine LWA. Engineering the gradation of LWA to meet ASTM required standard will allow the production of LWA from W-CCA a more attainable and practical product for the construction industry.